Seismic evidence for high pore pressures in the oceanic crust: Implications for fluid‐related embrittlement. Issue 10 (30th May 2013) - Shiina, Takahiro; Nakajima, Junichi; Matsuzawa, Toru
Abstract: [1] We estimated the P wave velocity structure of the crust of the subducting Pacific plate beneath northeast Japan using arrival time data of P ‐to‐ S ‐converted waves. The results show that the P wave velocity of the subducting crust varies along the arc and increases abruptly at a depth of ~100 km, from 6.5–7.0 km/s in the fore arc to 7.5–8.5 km/s in the back arc. The P wave velocity in the fore arc is ~10% lower than theoretically expected values for the metamorphosed mid‐ocean ridge basalt material. Seismicity in the subducting crust is most active at depths of 70–80 km where P wave velocities are lowest. The marked reduction of P wave velocity suggests the coexistence of aqueous fluids with hydrous minerals. Abundant fluids elevate pore fluid pressures and reduce effective normal stress, promoting intensive seismic activity in the low‐velocity crust. Our observations provide seismic evidence that earthquakes in the subducting crust are facilitated by fluid‐related embrittlement. Key Points: Estimation of Vp in the crust of the Pacific slab using PS‐converted waves Reduction in Vp in the forearc by ~10% from MORB model A link between crustal seismicity and low‐velocity in the subduting crust